The Effect of Teamwork, Work Motivation, and Work Discipline on Employee Performance at PT. Berkah Kawan Setya - M. Mafudz; Umar Burhan; Adiba Fuad Syamlan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of teamwork, work motivation, and work discipline on employee performance at PT. Berkah Kawan Setya, a medium-sized construction company. This study used a quantitative approach with a survey method, where data was collected through questionnaires distributed to 47 employees. Data analysis was conducted using multiple linear regression to determine the contribution of each independent variable to employee performance. The results showed that all three independent variables—teamwork, work motivation, and work discipline—have a positive and significant influence on employee performance. Of these, work discipline exerts the most dominant influence, followed by teamwork and work motivation. The coefficient of determination (R²) of 81.8% indicates that the variation in employee performance can be explained by these three behavioral factors, with the remainder influenced by other variables outside the model. These findings emphasize the importance of developing a disciplined, collaborative work environment that sustainably motivates employees. In the context of construction companies facing the challenges of dynamic teamwork and tight project targets, a human resource development strategy focused on behavioral aspects is crucial. This research provides empirical insights for HR management in designing policies that can increase productivity and support project success. Recommendations for companies include strengthening a culture of discipline, building strong team synergy, and providing incentives and rewards to enhance employee motivation.